Perplexity AI on the Writing Efficiency of EFL Students' in Higher Education: Students' Insight - Utami Lubis, Citra; Hz, Benni Icshanda Rahman (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Perplexity AI is a powerful machine learning technology that can be utilized to enhance students' writing skills. This study is aimed at investigating the effect of use Perplexed AI in the writing skills process from the perspective of students. This qualitative study employed two primary data collection methods: a modified questionnaire incorporating elements from specific teaching methods or learning approaches and semi-structured interviews. The adapted questionnaire was given to all students in their eighth semester studying English as a Foreign Language (EFL: English as A foreign Language) at a university in North Sumatra Province, and the obtained results include data about how students perceive and navigate the integration of AI in enhancing their writing efficiency within the realm of higher education, as revealed through the perspectives of the students. The results of this research can provide a strong foundation to support the implementation of perplexity artificial intelligence in the context of English language learning at the university level.